2020
DOI: 10.14814/phy2.14635
|View full text |Cite
|
Sign up to set email alerts
|

The serological responses to acute exercise in humans reduce cancer cell growth in vitro: A systematic review and meta‐analysis

Abstract: We systematically reviewed and meta‐analyzed the effects of acute exercise‐conditioned serum on cancer cell growth in vitro. Five literature databases were systematically searched for studies that measured cancer cell growth after exposure to human sera obtained before and immediately after an acute bout of exercise. Standardized mean differences (SMDs) with 95% confidence intervals (CIs) were pooled using a three‐level random‐effects model. Meta‐regressions were also performed with participant age and disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 57 publications
0
19
0
2
Order By: Relevance
“…This finding has since been replicated using LNCaP cells and sera derived from a comparable population (young healthy men) (Baldelli et al 2020), and it has also demonstrated in human breast cancer cell lines using sera derived from young healthy women and women with breast cancer (Baldelli et al 2020;Dethlefsen et al 2016Dethlefsen et al , 2017a, human colon cancer cell lines using sera derived from colon cancer survivors (Devin et al 2019), and human lung cancer cells using sera derived from healthy men (Kurgan et al 2017). Indeed, Orange et al (2020) recently summarised studies that had examined the effect of serum collected immediately post-exercise on in vitro cancer cell viability and, in a meta-analysis, reported an 8.6% decrease in cell viability compared with serum collected pre-exercise (Fig. 1).…”
Section: Effects Of Acute Exercisementioning
confidence: 71%
See 4 more Smart Citations
“…This finding has since been replicated using LNCaP cells and sera derived from a comparable population (young healthy men) (Baldelli et al 2020), and it has also demonstrated in human breast cancer cell lines using sera derived from young healthy women and women with breast cancer (Baldelli et al 2020;Dethlefsen et al 2016Dethlefsen et al , 2017a, human colon cancer cell lines using sera derived from colon cancer survivors (Devin et al 2019), and human lung cancer cells using sera derived from healthy men (Kurgan et al 2017). Indeed, Orange et al (2020) recently summarised studies that had examined the effect of serum collected immediately post-exercise on in vitro cancer cell viability and, in a meta-analysis, reported an 8.6% decrease in cell viability compared with serum collected pre-exercise (Fig. 1).…”
Section: Effects Of Acute Exercisementioning
confidence: 71%
“…This is perhaps unsurprising given the diverse range of populations, cancer cell lines, and exercise characteristics that have been included across different independent studies, all of which could be hypothesised to alter the presence and/or magnitude of the effect of exerciseconditioned serum on growth/viability. Interestingly, in the meta-analysis by Orange et al (2020), covarying for different cancer types (breast vs other), disease status (healthy vs cancer survivor), or exercise mode (continuous vs interval training) did not alter the effect magnitude or heterogeneity. However, these findings should be treated with some caution given the small number of studies included and the fact that this analysis was largely based on comparisons of effect sizes between independent studies (i.e.…”
Section: Effects Of Acute Exercisementioning
confidence: 86%
See 3 more Smart Citations